2016
DOI: 10.1158/1055-9965.epi-16-0316
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Preexisting Mental Health Disorders on the Diagnosis, Treatment, and Survival among Lung Cancer Patients in the U.S. Military Health System

Abstract: Background Higher cancer-related mortality has been observed among people with mental health disorders than in the general population. Both delay in diagnosis and inadequate treatment due to health care access have been found to explain the higher mortality. The U.S. Military Health System (MHS), in which all beneficiaries have equal access to health care, provides an ideal system to study this disparity where there are no or minimal barriers to health care access. This study assessed pre-existing mental healt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 57 publications
5
35
0
Order By: Relevance
“…Twenty-eight studies were included in this review and 24 in the meta-analysis (figure 1). Twenty-three studies were identified from 2381 possible MEDLINE citations6–11 13 17 39–53 and an additional five articles were identified through the PubMed search and a manual search of narrative review references 12 16 18 19 54. Sixteen studies investigated stage at diagnosis and 25 investigated survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-eight studies were included in this review and 24 in the meta-analysis (figure 1). Twenty-three studies were identified from 2381 possible MEDLINE citations6–11 13 17 39–53 and an additional five articles were identified through the PubMed search and a manual search of narrative review references 12 16 18 19 54. Sixteen studies investigated stage at diagnosis and 25 investigated survival.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of evidence supporting a greater risk of cancer-related death is based on a comparison of mortality rates in individuals with a psychiatric illness to a non-psychiatric population. Higher case-fatality rates have been reported in the few studies of cancer populations 6–19. Fewer studies have looked at cancer-specific death, which is important given the considerably higher baseline risk for death from non-cancer causes.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have found increased all-cause [2,8,[10][11][12][13][14][15][16][17] and cancer-specific mortality [18,19] among lung cancer patients with SMI, while some have reported difference in neither. [16,20,21] These conflicting results may reflect differences in study populations, designs and definitions.…”
Section: Introductionmentioning
confidence: 99%
“…Several scientific studies have been published regarding the prognosis of patients with cancer and MD, [5][6][7][8][9]11 most of which conclude that the presence of a MD increases the risk of cancer-related death. However, the aforementioned publications were all population-based studies using large databases.…”
Section: Discussionmentioning
confidence: 99%